A report on a survey among Portuguese Association of Interventional Cardiology associates regarding ionizing radiation protection practices in national interventional cath-labs - Costa, H (2023)
Introduction and objectives: Concerns surrounding the consequences of ionizing radiation (IR) have increased in interventional cardiology (IC). Despite this, the ever-growing complexity of diseases as well as procedures can lead to greater exposure to radiation. The aim of this survey, led by Portuguese Association of Interventional Cardiology (APIC), was to evaluate the level of awareness and current practices on IR protection among its members. Methods: An online survey was emailed to all APIC members, between August and November 2021. The questionnaire consisted of 50 questions focusing on knowledge and measures of IR protection in the catheterization laboratory. Results were analyzed using descriptive statistics. Results: From a response rate of 46.9%, the study obtained a total sample of 159 responses (156 selected for analysis). Most survey respondents (66.0%) were unaware of the radiation exposure category, and only 60.4% reported systematically using a dosimeter. A large majority (90.4%) employed techniques to minimize exposure to radiation. All participants used personal protective equipment, despite eyewear protection only being used frequently by 49.2% of main operators. Ceiling suspended shields and table protectors were often used. Only two-thirds were familiar with the legally established limit on radiation doses for workers or the dose that should trigger patient follow-up. Most of the survey respondents had a non-certified training in IR procedures and only 32.0% had attended their yearly occupational health consultation. Conclusions: Safety methods and protective equipment are largely adopted among interventional cardiologists, who have shown some IR awareness. Despite this, there is room for improvement, especially concerning the use of eyewear protection, monitoring, and certification. Keywords: Cardiologia de intervenção; Dosimeter; Dosímetro; Equipamentos de proteção; Intervention cardiology; Ionizing radiation; Limites de dose; Protective equipment; Radiação ionizante; Safety methods; Técnicas de minimização.